Violations of Grice’s Conversational Maxims in Japanese Fictional Discourse: A Case Study of the Anime Bofuri - Nurul Rahmah Alfathonah; Thamita Islami Indraswari (KIRYOKU, 2026)
This study investigates violations of Grice’s Cooperative Principle and the particularized conversational implicatures they generate in the anime Bofuri: I Don’t Want to Get Hurt, so I’ll Max Out My Defense (season one). Focusing on dialogues between Maple and Sally, twelve episodes were analyzed using a qualitative descriptive approach and a listen-and-record technique. The findings indicate that violations of the maxims of quantity, quality, relation, and manner are employed strategically, producing implicatures such as sarcasm, refusal, concern, and evasion. These implicatures contribute to character development and relational dynamics, reflecting the indirectness and affective stance characteristic of Japanese discourse. By mapping specific maxim violations to their corresponding implicatures, the study offers a nuanced understanding of pragmatic mechanisms in fictional interaction and narrative communication.